URGENSI CIVIL FORFEITURE UNTUK MENINGKATKAN PENGEMBALIAN KERUGIAN KEUANGAN NEGARA - Sonya Airini Batubara; Suhaila Zulkifili Zulkifli zulkifli (jurnal.unprimdn.ac.id, 2018)
The criminal act of corruption includes the crime of extra ordinary crime. Based on Law no. 31 of 1999 in conjunction with Act no. 20 Year 2001 on the Eradication of Corruption. State financial losses due to corruption are still not covered and public unrest is still high against law enforcement of corruption in Indonesia. Asset recovery is a system of law enforcement committed by victim state of corruption to deprive, deprive, eliminate the right to assets of corruption from corruption actors through a series of processes and mechanisms. Efforts to restore the proceeds of crime or criminal acts of corruption constitute an act of deprivation as an additional criminal offense on a criminal court judge's judgment against the property owned by a convicted criminal of corruption, asset recovery efforts also require international cooperation, both bilateral and multilateral cooperation due to the return of assets outside Indonesia's territorial territory would require mutual cooperation or assistance in criminal matters. (mutual legal assistance / MLA).